(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study was conducted to determine the colony forming units (CFU) to isolate, identify, and antibiotic sensitivity of Staphylococcus aureus from chicken nuggets (CN). Materials and Methods: Sixty CN samples from two brands were collected from different superstores in Mymensingh, Bangladesh. Uncooked, oven-cooked (OC), or gas stove-cooked (GSC) CN samples were inoculated onto mannitol salt agar and blood agar. Results: The total staphylococcal count (TSC) for uncooked CN ranged from log 4.68 to log 5.11 CFU/gm. For OC CN, TSC ranged from log 3.29 to log 3.62 CFU/gm. For GSC CN, TSC ranged from log 3.09 to log 3.49 CFU/gm. Relative to uncooked CN, microwave oven-cooked and GSC samples significantly reduced the TSC of CN(p < 0.01). Using the polymerase chain reaction assay and standard biochemical testing, only 8 out of 60 CN samples contained S. aureus. Staphylococcus aureus were resistant to Ampicillin (100%), Amoxicillin (100%), Oxacillin (75%), Cefixime (87.5%), Doxycycline (75%), intermediately sensitive to Erythromycin (25%), Cephalexin (12.5%), Ciprofloxacin (25%), Gentamicin (12.5%), Doxycycline (12.5%) and sensitive to Oxacillin (25%), Azithromycin (100%), Erythromycin (75%) Cephalexin (87.5%), Cefixime (12.5%), Chloramphenicol (100%), Ciprofloxacin (75%), Gentamicin (87.5%), Doxycycline (12.5%), and Vancomycin (100%). Conclusion: This study reports the first isolation and identification of S. aureus from CN in Bangladesh. GSC CN was better than OC and uncooked CN. Data also suggest that CN is contaminated with multidrug-resistant S. aureus, which poses a public health hazard. J. Adv. Vet. Anim. Res., 9(4): 601–609, December 2022 http://doi.org/10.5455/javar.2022.i629